2018
DOI: 10.1016/j.ymgme.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Tissue acylcarnitine status in a mouse model of mitochondrial β-oxidation deficiency during metabolic decompensation due to influenza virus infection

Abstract: Despite judicious monitoring and care, patients with fatty acid oxidation disorders may experience metabolic decompensation due to infection which may result in rhabdomyolysis, cardiomyopathy, hypoglycemia and liver dysfunction and failure. Since clinical studies on metabolic decompensation are dangerous, we employed a preclinical model of metabolic decompensation due to infection. By infecting mice with mouse adapted influenza and using a pair-feeding strategy in a mouse model of long-chain fatty acid oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
(49 reference statements)
1
25
0
Order By: Relevance
“…However, the reductions of MG in both PFC and striatum were not normalized by rTMS, suggesting that the glycerolipids in the PFC and striatum are more vulnerable than hippocampus to CPZ. AcCa compounds in the brain functionally alter and stabilize membranes, improving mitochondrial function and increasing antioxidant activity ( Rutkowsky et al, 2014 ; Tarasenko et al, 2018 ). The present study also found that CPZ treatment decreased the levels of AcCa only in the PFC, which was normalized by rTMS, suggesting that the AcCa in the PFC are more vulnerable than other brain region and might be associated to the therapeutic effects of rTMS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the reductions of MG in both PFC and striatum were not normalized by rTMS, suggesting that the glycerolipids in the PFC and striatum are more vulnerable than hippocampus to CPZ. AcCa compounds in the brain functionally alter and stabilize membranes, improving mitochondrial function and increasing antioxidant activity ( Rutkowsky et al, 2014 ; Tarasenko et al, 2018 ). The present study also found that CPZ treatment decreased the levels of AcCa only in the PFC, which was normalized by rTMS, suggesting that the AcCa in the PFC are more vulnerable than other brain region and might be associated to the therapeutic effects of rTMS.…”
Section: Discussionmentioning
confidence: 99%
“…Acylcarnitine is the main transporter involved in the energy production process. It carries activated longchain fatty acids (the breakdown products of fatty acids and amino acids) into mitochondria for the β-oxidation process (Tarasenko et al, 2018). Acylcarnitine also serves as an important biomarker of mitochondrial dysfunction with an increase of acylcarnitines (Chen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The main function of acylcarnitines is involved in long-chain fatty acids (LCFAs) β-oxidation ( Figure 2 ). They serve as carriers to transport activated LCFAs into mitochondria for subsequent β-oxidation to provide energy for cell activities [ 29 ]. The enzymes that regulate these processes are mainly long-chain acyl-coenzyme A synthetase (LACS), carnitine/acylcarnitine translocase (CACT), carnitine palmitoyl-transferase 1 and 2 (CPT1 and CPT2) [ 30 ].…”
Section: Function Of Acylcarnitines In Cellular Metabolismmentioning
confidence: 99%